2006
DOI: 10.1111/j.1527-5299.2006.05477.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐Blocker Therapy for Heart Failure: Should the Therapeutic Target Be Dose or Heart Rate Reduction?

Abstract: Therapeutic target with β blockers in heart failure, i.e., target heart rate reduction or β‐blocker dose, is controversial. To resolve this controversy, the authors studied 152 heart failure patients on β blockers who were divided into four groups based on median peak exercise heart rate reduction as compared with predicted and prescription of at least 50% recommended β‐blocker dose. Event‐free survival (vs. death or assist device placement or urgent transplantation) was compared. Baseline and peak exercise he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…These studies showed incremental benefit of increasing doses of BB with respect to improvement in LVEF and reduction in CV mortality . There has been long‐standing debate as to whether the benefits of BB are solely related to HR reduction vs alternative mechanisms, with the therapeutic value likely being multifactorial . In our study, target doses of BB therapy were more frequently achieved in patients whose LV function recovered, and we found a relationship between achievement of target doses of BB and freedom from the composite endpoint of all‐cause mortality and HF hospitalizations.…”
Section: Discussionsupporting
confidence: 49%
“…These studies showed incremental benefit of increasing doses of BB with respect to improvement in LVEF and reduction in CV mortality . There has been long‐standing debate as to whether the benefits of BB are solely related to HR reduction vs alternative mechanisms, with the therapeutic value likely being multifactorial . In our study, target doses of BB therapy were more frequently achieved in patients whose LV function recovered, and we found a relationship between achievement of target doses of BB and freedom from the composite endpoint of all‐cause mortality and HF hospitalizations.…”
Section: Discussionsupporting
confidence: 49%
“…As a result, it was suggested that the HR-lowering effect of β-blockers was a major contributor to the clinical benefit associated with these agents. In a study of 152 patients with HF who were receiving β-blocker therapy, greater reductions in HR were associated with better clinical outcomes for patients overall, and higher β-blocker doses provided additional clinical benefits among patients with persistently elevated HR 39. These results suggest that the magnitude of reduction in HR may be more important than achieving the target dose of β-blocker therapy in patients with HF 38,39.…”
Section: Heart Rate Control In Heart Failurementioning
confidence: 96%
“…In a study of 152 patients with HF who were receiving β-blocker therapy, greater reductions in HR were associated with better clinical outcomes for patients overall, and higher β-blocker doses provided additional clinical benefits among patients with persistently elevated HR 39. These results suggest that the magnitude of reduction in HR may be more important than achieving the target dose of β-blocker therapy in patients with HF 38,39. In the Cardiac Insufficiency BIsoprolol Study (CIBIS), treatment of 557 patients with bisoprolol reduced HR by approximately 15 beats/minute relative to placebo ( P < 0.001), and HR change was the most powerful predictor of survival ( P < 0.01) 40.…”
Section: Heart Rate Control In Heart Failurementioning
confidence: 99%
“…As a result, it was suggested that RHR lowering effect of beta-blockers was a major contributor to the clinical benefit associated with these agents. A study of 152 patients with heart failure who were receiving beta-blocker therapy showed that higher beta-blocker doses provided additional clinical benefits among patients with persistently elevated RHR 24 . These results suggest that the magnitude of reduction in RHR may be more important than achieving the target dose of beta-blocker therapy in patients with heart failure 24 .…”
Section: Benefits Of Pharmacological Reduction Of Heart Ratementioning
confidence: 99%